AKTIVITAS DAYA HAMBAT DAN ELUSIDASI GOLONGAN SENYAWA EKSTRAK DAUN KELOR (Moringa oleifera L.) TERHADAP BAKTERI Staphylococcus aureus ATCC - Wahyuning Dwi Putri; Ida Bagus Gede Darmayasa; Ni Made Susun Parwanayoni (Program Studi Biologi Universitas Udayana, 2024)
Inappropriate use of antibacterial drugs can cause resistant bacteria. One of the efforts made in reducing the occurrence of resistance is to utilize plants that contain antibacterial compounds, one of which is Moringa leaves (Moringa oleifera L.). This study aims to determine the ability of moringa leaf crude extract in inhibiting the growth of Staphylococcus aureus ATCC bacteria and the class of compounds contained in moringa leaf extract. Moringa leaf crude extract was macerated with 96% ethanol and tested using the well diffusion method. The concentrations of moringa leaf extract used were 25% (b/v), 15% (b/v), 10% (b/v), 5% (b/v), negative control (96% ethanol), and positive control (ciprofloxacin) and MIC (Minimum Inhibitor Concentration) test. Moringa leaf extract at a concentration of 25% (b/v) was able to form an inhibition zone against S. aureus ATCC bacteria with a diameter of 15.81mm and MIC concentration of 2% (b/v) formed an inhibition zone diameter of 6.17mm. The Lethal Concentration 50 (LC50) value of moringa leaf extract against S. aureus ATCC bacteria is 1.68%. Moringa leaf extract contains alkaloid, saponin, steroid, flavonoid, tannin and phenolic compounds.